Mechanisms of drug resistance in mycobacterium tuberculosis - Mary Margaret Wade; Ying Zhang (2004)
Tuberculosis is a worldwide health problem posing increasing threat with the spread of HIV infection and drug resistant Mycobacterium tuberculosis strains. Consequently, control of this disease has become a significant challenge despite the availability of chemotherapy and BCG vaccine. Drug resistance for all first-line anti-tuberculosis agents and some second-line agents has been observed. Moreover, the occurrence of strains of M. tuberculosis resistant to multiple anti-tuberculosis drugs is increasing. Mechanisms of action and resistance of major anti-tuberculosis drugs are reviewed. In addition, the phenotypic drug resistance such as dormant or persistent tubercle bacilli and its importance are also emphasized. In order to combat the threat of drug resistant tuberculosis and to more effectively control the disease, an understanding of the mechanisms underlying drug resistance is necessary. This knowledge could be used for the development of molecular tests for rapid detection of drug resistant bacilli and future anti-tuberculosis drugs.